2016
DOI: 10.1523/jneurosci.3220-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mirror Neurons of Ventral Premotor Cortex Are Modulated by Social Cues Provided by Others' Gaze

Abstract: Mirror neurons (MNs) in the inferior parietal lobule and ventral premotor cortex (PMv) can code the intentions of other individuals using contextual cues. Gaze direction is an important social cue that can be used for understanding the meaning of actions made by other individuals. Here we addressed the issue of whether PMv MNs are influenced by the gaze direction of another individual. We recorded single-unit activity in macaque PMv while the monkey was observing an experimenter performing a grasping action an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 59 publications
3
18
0
2
Order By: Relevance
“…There is also evidence for mirroring activity in newborn monkeys when they observe communicative facial gestures (Ferrari et al, 2012). And, as noted earlier, monkey mirror neurons are modulated by eye gaze (Coudé et al, 2016), a key feature in communicative contexts across species. In the last decade, there have been a number of studies demonstrating that macaques can learn to partially control vocalization, with a very limited number of utterances (Coudé et al, 2011;Hage & Nieder, 2013).…”
Section: From Mirror Neurons In Monkeys To Human Language: Beyond Tsupporting
confidence: 57%
“…There is also evidence for mirroring activity in newborn monkeys when they observe communicative facial gestures (Ferrari et al, 2012). And, as noted earlier, monkey mirror neurons are modulated by eye gaze (Coudé et al, 2016), a key feature in communicative contexts across species. In the last decade, there have been a number of studies demonstrating that macaques can learn to partially control vocalization, with a very limited number of utterances (Coudé et al, 2011;Hage & Nieder, 2013).…”
Section: From Mirror Neurons In Monkeys To Human Language: Beyond Tsupporting
confidence: 57%
“…The suggestion that processing eye-gaze direction and wider social orienting mechanisms could occur via mirroring or direct mapping processes has, however, attracted growing interest (Frischen, Loach, & Tipper, 2009;Rizzolatti & Sinigaglia, 2010;Shepherd, 2010). One recent fMRI study has already identified mirror neuron areas which may be responsive to averted and direct gaze in humans (Coudé et al, 2016).…”
Section: The Neural Basis Of Attention To Actionmentioning
confidence: 99%
“…Biological motion is linked to mirror neurons in the context of action understanding (e.g., [82, 83]), recognition of facial expressions has been linked to mirror neurons in an emulation account (e.g., [79]), and eye gaze processing and gaze following have been linked to mirror neuron activity [84, 85]. …”
Section: Left Inferior Frontal and Precentral Gyrus/mirror Neuronmentioning
confidence: 99%